1996
DOI: 10.3719/weed.41.31
|View full text |Cite
|
Sign up to set email alerts
|

Safening Mechanism of Dymron and Dimepiperate on Azimsulfuron-Treated Rice.

Abstract: Safening effect of two herbicides, dymron (1-(a, a-dimethylbenzyl)-3-ptolylurea and dimepiperate (S-(1-methyl-1-onyl]-urea)-treated rice and the effect of the two compounds on absorption and metabolism of azimsulfuron in the plant were determined. While treatment of azimsulfuron at very high dosage (64-125g a.i./ha) reduced the dry weight of rice shoots, simultaneous treatment with dymron at 450g a.i./ha or dimepiperate at 3,000g a.i./ha caused their recovery from the azimsulfuron injury. Dymron and dimepipera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The O ‐dealkylation reaction is considered to be a major detoxicative metabolic reaction, and is a contributing factor of SU herbicide selectivity. This oxidative O ‐demethylation reaction is assumed to be catalyzed by NADPH‐dependent mono‐oxygenase, cytochrome P‐450, by the experimental evidences that inhibitors of P‐450 activiy, piperonyl butoxide (PBO) or aminobenzotriazole (ABT) increased the phytotoxicity of bensulfuron‐methyl and azimsulfuron (Shirakura et al 1996). Because the P‐450 activity in plants is low, there are few direct evidences that O ‐dealkylation of SU are catalyzed by P‐450, although many numbers of P‐450 species are known to be involved in pesticide metabolism (Ohkawa et al 1999).…”
Section: Metabolism Of Rice Herbicides In Plantsmentioning
confidence: 99%
“…The O ‐dealkylation reaction is considered to be a major detoxicative metabolic reaction, and is a contributing factor of SU herbicide selectivity. This oxidative O ‐demethylation reaction is assumed to be catalyzed by NADPH‐dependent mono‐oxygenase, cytochrome P‐450, by the experimental evidences that inhibitors of P‐450 activiy, piperonyl butoxide (PBO) or aminobenzotriazole (ABT) increased the phytotoxicity of bensulfuron‐methyl and azimsulfuron (Shirakura et al 1996). Because the P‐450 activity in plants is low, there are few direct evidences that O ‐dealkylation of SU are catalyzed by P‐450, although many numbers of P‐450 species are known to be involved in pesticide metabolism (Ohkawa et al 1999).…”
Section: Metabolism Of Rice Herbicides In Plantsmentioning
confidence: 99%
“…may be dependent on cytochrome P-450 reactions (Shim et al 1990b). Dymron may display safening effects partially by enhancing the metabolism of not only a sulfonylurea herbicide, but also a chloroacetamide herbicide via enhancing cytochrome P-450 activity, as well as dimepiperate (Nishizaka et al 1991;Shirakura et al 1988Shirakura et al , 1996Yun et al 1999). Dymron is also known to reduce the uptake of bensulfuron-methyl by rice seedlings .…”
Section: Concentrationmentioning
confidence: 99%
“…Pretilachlor is a chloroacetamide herbicide commonly used to control some broadleaf weeds and annual grasses in transplanted ricefields (Murakami 1990). Dymron [1‐(α,α‐dimethybenzyl)‐3‐( p ‐tolyl)urea], an urea herbicide (sedge killer), however, is known to protect rice from injury caused by chloroacetamide herbicides, pretilachlor and thenylchlor (Ogasawara et al 1991), as well as sulfonylurea herbicides, bensulfuron methyl and azimsulfuron (Nishizaka et al 1991; Shirakura et al 1996), and dymron may enhance oxidative or cytochrome P‐450 activity in rice. However, Omokawa et al (1996 ) reported that dymron reduced the uptake of bensulfuron‐methyl by rice seedlings, and quantitative changes in the metabolism of bensulfuron‐methyl by safened rice seedlings were observed, but these did not appear to support the involvement of enhanced herbicide metabolism in the safening action of dymron.…”
Section: Introductionmentioning
confidence: 99%
“…However, the GST activity might not play a major role in the safening action of dymron on pretilachlor injury (Deng et al 2001). In contrast, the safening action of dymron against sulfonylurea herbicides such as azimsulfuron [1‐(4,6‐dimethoxypyrimidin‐2‐yl)‐3‐[2‐methyl‐4‐(2‐methyl‐2 H ‐tetrazol‐5‐yl)‐2 H ‐pyrazole‐3‐sulfonyl]urea] and bensulfuron‐methyl [methyl‐2‐[[[[[(4,6‐dimethoxypyrimidin‐2‐yl)‐amino]‐carbonyl]‐amino]‐sulfonyl]‐methyl]‐benzoate] on rice seedlings was induced by the enhancement of O ‐demethylation of both herbicides (Shirakura et al 1996) and the reducing absorption of bensulfuron‐methyl into the seedlings (Omokawa et al. 1996).…”
Section: Introductionmentioning
confidence: 99%